Isolation of the oleaginous yeasts from the soil and studies of their lipid-producing capacities - Pan, Li-Xia (Array, 2009)
Summary: D-xylose is one of the most abundant pentose sugars in nature. To isolate oleaginous yeasts that can utilize xylose from diverse soil samples, soils from a litchi orchard, longan orchard, carambola orchard, and woods were collected, yeasts were isolated by the glycerol enrichment and their xylose-assimilating capacities were measured. A subset of these isolates was grown in nitrogen-limited media and then screened for potential oleaginous yeasts by the Sudan Black B staining, after which their lipid-producing capacities were studied. There were 13 strains of oleaginous yeasts identified, and a rapid microbiological assay was provided to exploit microbial lipids that may one day be used as biodiesels or cocoa butter substitute